The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10856-016-5741-2
|View full text |Cite
|
Sign up to set email alerts
|

A superhydrophilic titanium implant functionalized by ozone gas modulates bone marrow cell and macrophage responses

Abstract: Bone-forming cells and Mϕ play key roles in bone tissue repair. In this study, we prepared a superhydrophilic titanium implant functionalized by ozone gas to modulate osteoconductivity and inhibit inflammatory response towards titanium implants. After 24 h of ozone gas treatment, the water contact angle of the titanium surface became zero. XPS analysis revealed that hydroxyl groups were greatly increased, but carbon contaminants were largely decreased 24 h after ozone gas functionalization. Also, ozone gas fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 41 publications
2
21
1
Order By: Relevance
“…The surface topography/roughness, hydrophilicity, and chemical composition potentiate cellular responses to materials [6,7,9,[36][37][38][39]. However, in the present study, all of the functionalized surfaces showed similar surface topography/roughness to those of bare PEEK, and thus can be excluded as a factor in the observed differences of MSCs behaviors on the functionalized PEEK.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…The surface topography/roughness, hydrophilicity, and chemical composition potentiate cellular responses to materials [6,7,9,[36][37][38][39]. However, in the present study, all of the functionalized surfaces showed similar surface topography/roughness to those of bare PEEK, and thus can be excluded as a factor in the observed differences of MSCs behaviors on the functionalized PEEK.…”
Section: Discussioncontrasting
confidence: 49%
“…Alternatively, PEEK has a highly hydrophobic surface, but surfaces became more hydrophilic after surface functionalization. It is widely accepted that a hydrophilic surface produced a more pronounced effect on the cell responses than a hydrophobic surface [36][37][38][39]. Notably, the O 3 -Ca and O 3 -PCa showed enhanced cell proliferation compared with the bare at three and seven days.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On hydrophilic implant surfaces, molecules are adsorbed in a more flexible pattern, leading to an enhanced interaction between the implant surface and the surrounding environment. Previous studies reported that hydrophilic surfaces demonstrated anti-inflammatory property by mitigating the pro-inflammatory cytokines production and inflammatory response of macrophages 23 24 . Since surface chemistry influences surface wettability 22 , the surface chemistry may be the most critical factor in modulating DC response.…”
Section: Discussionmentioning
confidence: 99%
“…Preparing a superhydrophilic titanium implant functionalised with ozone gas can modulate osteoconductivity and inhibit the inflammatory response to titanium implants. This superhydrophilic surface has been proposed to be useful as an endorsed implantable biomaterial and as a biomaterial for implantation in other tissues (13). The effect of ozone treatment in combination with autogenous bone grafts on bone healing in rat calvaria has been investigated.…”
Section: Introductionmentioning
confidence: 99%